Wooden Penetrating Pelvic Trauma Passing the Foramen Ischiadicum - Benedikt Ruben Abel; Heinz-Lothar Meyer; Roman Müller; Katharina Henze; Marcel Dudda; Max Daniel Kauther (Case Reports in Orthopedics)
We describe the case of a 45-year-old woman who suffered an impalement injury of the pelvis with penetration of the sciatic foramen by a wooden foreign body. Following a single operation, the injury healed without complications or infection. We have taken this as an opportunity to describe the case and our standard procedure in more detail.